(untitled) (Journal of Management and Social Sciences, 2025)
Nigeria, as the largest economy in Africa, grapples with systemic corruption and governance failure, providing fertile ground for criminal activities like kidnapping for ransom. This study examines the nexus between corruption, governance failure, and the surge in kidnapping, employing a qualitative research method. Using crime data extracted from media reports, trends and patterns of ransom kidnappings are analyzed. The findings reveal a notable increase in the commercialization of kidnapping spurred by various socio-economic and political factors including poverty, unemployment, poor security architecture, lax law enforcement, and corruption. This proliferation of ransom kidnappings exacerbates insecurity, posing threats to personal safety and economic stability. The study advocates for holistic reforms to combat corruption and enhance good governance in Nigeria. Strategies recommended among others include the overhauling of the nations’ security architecture, bolstering of law enforcement, transparency and accountability in governance, engagement of traditional rulers in governance and collaboration between governmental bodies and civil societies.